2000
DOI: 10.1128/iai.68.9.5068-5074.2000
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Antibodies toCryptosporidium parvumin Healthy Volunteers

Abstract: This study examined the intestinal antibody response in 26 healthy volunteers challenged with Cryptosporidium parvum oocysts. Fecal extracts were assayed for total secretory immunoglobulin A (IgA) and C. parvumspecific IgA reactivity. Specific IgA reactivity was standardized to IgA concentration and expressed as a reactivity index (RI). Anti-C. parvum fecal IgA (fIgA) increased significantly in 17 of 26 (65.4%) following oocyst ingestion. Of those with detectable responses, 59, 76.5, and 94.1% were positive by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…A previous study using oocysts as the antigen found that Cryptosporidium-specific fecal IgA antibody responses in human volunteers correlated significantly with the presence of active or recent infection. 74 There were several limitations to this study. The numbers of subjects in each group were small.…”
Section: Discussionmentioning
confidence: 94%
“…A previous study using oocysts as the antigen found that Cryptosporidium-specific fecal IgA antibody responses in human volunteers correlated significantly with the presence of active or recent infection. 74 There were several limitations to this study. The numbers of subjects in each group were small.…”
Section: Discussionmentioning
confidence: 94%
“…Antibodies have also been detected in fecal fluid, including from experimentally infected volunteers (Kapel et al 1993;Dann et al 2000). It was suggested that this might be more sensitive than detection of humoral antibody but this has been disputed ).…”
Section: )mentioning
confidence: 99%
“…They remain present for several weeks (S. M. Dann, unpublished data). Fecal IgA was detected in the stools of adult volunteers up to 6 weeks after infection (17). Serum IgG, IgA, and IgM antibody responses are usually directed against soluble or membrane-associated sporozoite proteins (65,74); IgA reacts mostly to 17-kDa proteins (69,76), IgM reacts mostly to 27-kDa proteins, and IgG reacts mostly to 17-, 27-, and 15-kDa proteins (69).…”
Section: B Cells and Antibodiesmentioning
confidence: 99%